Between Lifestyle and Financial Responsibility: The Moderating Effect of Financial Imprudence in Islamic Higher Education Contexts - Perdana, Indri; Iiz Izmuddin (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: This study aims to examine the influence of lifestyle on personal financial management, with financial imprudence serving as a moderating variable. The focus is on students at Islamic State Higher Education Institutions (PTKIN) in West Sumatra, where increasing consumer behavior raises concerns about financial discipline among young adults. Method: A quantitative survey method was employed, with data collected through a Likert-scale questionnaire distributed via Google Forms. The population consisted of PTKIN students in West Sumatra. A total of 288 responses were collected, with 271 valid after data screening. Sampling was conducted using the Rao Purba formula. Data were analyzed using the Warp Partial Least Squares method through WarpPLS 7.0 software. Result: Findings indicate that lifestyle has a positive and significant effect on personal financial management (p-value = 0.056 < 0.05). Additionally, financial imprudence moderates the relationship between lifestyle and financial management, as evidenced by an interaction coefficient of 0.080. While the moderating effect is statistically significant, it is relatively small in magnitude.Conclusion: Lifestyle significantly shapes how individuals manage their personal finances. A more balanced lifestyle tends to support better financial practices. Furthermore, financial imprudence—as a reflection of excessive or wasteful spending—can either strengthen or diminish this relationship, suggesting its critical yet nuanced role in financial behavior dynamics.